AN EMPIRICAL ANALYSIS OF THE EFFECT OF CORPORATE GOVERNANCE ON THE FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA - Bamidele Vincent Olawale (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The research investigated the impact of corporate governance on the financial performance of deposit banks in Nigeria. The study specifically investigates the impact of audit committee effectiveness on the return on assets of selected deposit money banks in Nigeria, analyzes the influence of board committee meeting frequency on the return on assets of these banks, and examines the effect of board committee size on the return on assets of the selected deposit money banks in Nigeria. Purposive sampling was employed to choose five (5) deposit money banks in Nigeria. Data were collected from the published audited annual financial statements of the selected Deposit Money Banks listed in the Nigeria Exchange Group Factbook over a 10-year period, from 2013 to 2024. This research employed descriptive and inferential analysis through correlation analysis and panel regression estimates. A Hausman test was performed to determine the most consistent estimation method, revealing that the fixed effect model is the most appropriate for the analysis. The findings indicated a coefficient and probability of 0.0032 and 0.2133 (p > 0.05) for ACEFF, suggesting that audit committee effectiveness exerted an insignificant positive influence on financial performance. The findings indicated a coefficient of 0.0014 and a probability of 0.4776 (p > 0.05) for BMEET, signifying that the board meeting exerted an insignificant positive influence on financial performance. The results indicate a negative and insignificant relationship between BSIZE and ROA, with a coefficient of -0.0014 and a p-value of 0.6000. The study determined that audit committee effectiveness (ACEFF) and board meetings (BMEET) exerted a positive yet insignificant influence on the return on assets (ROA) of the chosen deposit money banks. The study indicates that listed deposit money institutions should meticulously comply with the mandated board size to enhance financial performance.